Editorial (Intervention. European Journal of Economics and Economic Policies, 2008)
The present issue focuses on three main areas. In the Forum there is a first focus containing three case studies in economic policies. Nigel F.B. Allington and John S.L. McCombie examine the relationship between productivity growth and unemployment in the UK during the Thatcher era. Thomas Bernhardt discusses political-economy interpretations of the Argentinean crisis 2001/02, and Karin Fischer deals with the impact of policy reforms on income distribution in Honduras. A second focus, also in the Forum, is composed of four contributions which deal with recent interpretations of Keynes's oeuvre. Victoria Chick and Jan Toporowski review and discuss two reinterpretations of Keynes's main book, the General Theory, by Michael S. Lawlor and Geoff Tily. We also pick up Paul Davidson's perspective on Keynes again. In the last issue, Peter Spahn reviewed John Maynard Keynes, the latest monograph by Paul Davidson, which summarises his interpretation of Keynes's theory. This has provoked a comment by Paul Davidson which we publish together with a reply by Peter Spahn. The interview with Jan Kregel which opens the Forum can also be considered to be part of this second focus. Kregel explains how in his academic career he has tried to mediate between different strands of reading Keynes's theory and between different Post-Keynesian schools. The Forum is completed by a contribution on the Post Keynesian Economics Study Group, which has pushed the development of the Post-Keynesian research programme, in particular in the UK, for 20 years now.
Keywords: 330